AB0410 Effect of Anti-Tumor Necrosis Factor Alpha Treatment of Rheumatoid Arthritis and Chronic Kidney Disease. (10th June 2014) - Moon, S.; Park, E.-J.; Kim, H.W.; Shin, K.-S.; Lee, C.-K.; Choe, J.-Y.; Cha, H.-S.; Kim, J.
Abstract : Background: Rheumatoid arthritis (RA) and chronic kidney disease (CKD) are very prevalent and so often coincide. Among various anti-inflammatory agents, TNF-α blocking drugs reportedly stabilize renal function in RA patients with CKD and/or secondary renal amyloidosis by suppressing inflammation. However, there are no available data supporting the efficacy of anti-TNF-α agents in a larger population of RA patients with renal insufficiency. Objectives: To investigate the impact of anti-tumor necrosis factor alpha (TNF-α) therapy on progression of CKD in patients with RA. Methods: Seventy patients with RA and CKD were retrospectively analyzed. Outcomes were evaluated using the difference in the annual change of estimated glomerular filtration rate (eGFR) between patients with treated with anti-TNF-α or without. Results: There was a tendency toward stabilization of eGFR after a median of 2.6 years (interquartile range, 1.2–4.2 years) from 50.3±8.4 ml/min/1.73 m 2 to 54.5±16.0 ml/min/1.73 m 2 in patients received anti-TNF-α therapy (p=0.084). Conversely, eGFR decreased significantly in patients not receiving anti-TNF-α therapy after a median of 3.0 years (interquartile range, 1.8–4.6 years) from 50.9±7.7 ml/min/1.73 m 2 to 43.7±10.9 ml/min/1.73 m 2 (p<0.001). The annual change of eGFR was significantly different between patients treated with anti-TNF-α drugs and without (2.0±7.0 ml/min/1.73 m 2 /y versus -2.9±5.8 ml/min/1.73 m 2 /y; difference in mean values, -4.9 ml/min/1.73 m 2 /y; 95% confidence interval, -7.5 to -2.2; p=0.002). Use of anti-TNF-α drugs was also significantly associated with positive annual change of eGFR in logistic regression analysis (p=0.009). Conclusions: Among patients with RA and CKD, treatment with anti-TNF-α drugs was associated with less renal function decline. Anti-TNF-α drugs may be beneficial for managing RA combined with CKD. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4801